2012
DOI: 10.1038/npp.2012.115
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of GABAA Receptor Subtypes in Benzodiazepine-Induced Enhancement of Brain-Stimulation Reward

Abstract: Benzodiazepines such as diazepam are widely prescribed as anxiolytics and sleep aids. Continued use of benzodiazepines, however, can lead to addiction in vulnerable individuals. Here, we investigate the neural mechanisms of the behavioral effects of benzodiazepines using the intracranial self-stimulation (ICSS) test, a procedure with which the reward-enhancing effects of these drugs can be measured. Benzodiazepines bind nonselectively to several different GABA A receptor subtypes. To elucidate the a subunit(s)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
2
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 47 publications
3
43
2
2
Order By: Relevance
“…Under cocaine baseline conditions, our findings are consistent with the prediction advanced by Tan et al (2010) that a1-sparing compounds should be without reinforcing effects, possibly due to a lack of disinhibition of VTA dopaminergic neurons that innervate the NAc. In contrast, our findings that a1-sparing compounds have reinforcing effects under the midazolam baseline condition is more consistent with recent results reported by Reynolds et al (2012), in which the a1GABA A receptor appeared to have little role in benzodiazepine-induced enhancement of reward thresholds in an intra-cranial self-stimulation procedure.…”
Section: Discussionsupporting
confidence: 92%
“…Under cocaine baseline conditions, our findings are consistent with the prediction advanced by Tan et al (2010) that a1-sparing compounds should be without reinforcing effects, possibly due to a lack of disinhibition of VTA dopaminergic neurons that innervate the NAc. In contrast, our findings that a1-sparing compounds have reinforcing effects under the midazolam baseline condition is more consistent with recent results reported by Reynolds et al (2012), in which the a1GABA A receptor appeared to have little role in benzodiazepine-induced enhancement of reward thresholds in an intra-cranial self-stimulation procedure.…”
Section: Discussionsupporting
confidence: 92%
“…In an earlier study, we showed that zolpidem did not cause reward enhancement in ICSS (Reynolds et al, 2012), whereas our current findings show that the a1GABA A Rs are required for the reward-enhancing actions of midazolam. This could be interpreted as the a1GABA A Rs being required, but not sufficient for, reward enhancement.…”
Section: Discussioncontrasting
confidence: 92%
“…The ICSS paradigm is based on the operant response of the animals to brain stimulation and can be viewed as the animals' willingness to work to obtain a certain level of stimulation. Although animals will learn operant responses that elicit stimulation in a large number of different brain areas (Zacharko et al, 1990), the medial forebrain bundle was selected in the current study because of the relative lack of motor artifacts upon stimulation in this region, as well as for comparability to earlier studies from our laboratory using other benzodiazepines (Straub et al, 2010;Reynolds et al, 2012). Responding to lower stimulation frequencies after the administration of a drug than those that maintained responding previously is interpreted as 'reward enhancement', and is commonly observed after the administration of drugs of abuse (Wise, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations